CD5 Surface Expression Marks Intravascular Human Innate Lymphoid Cells That Have a Distinct Ontogeny and Migrate to the Lung - Alisjahbana, Arlisa; Gao, Yu; Sleiers, Natalie; Evren, Elza; Brownlie, Demi; von Kries, Andreas; Jorns, Carl; Marquardt, Nicole; Michaëlsson, Jakob; Willinger, Tim (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILCs) contribute to immune defense, yet it is poorly understood how ILCs develop and are strategically positioned in the lung. This applies especially to human ILCs due to the difficulty of studying them in vivo. Here we investigated the ontogeny and migration of human ILCs in vivo with a humanized mouse model (“MISTRG”) expressing human cytokines. In addition to known tissue-resident ILC subsets, we discovered CD5-expressing ILCs that predominantly resided within the lung vasculature and in the circulation. CD5+ ILCs contained IFN-producing mature ILC1s as well as immature ILCs that produced ILC effector cytokines under polarizing conditions in vitro. CD5+ ILCs had a distinct ontogeny compared to conventional CD5- ILCs because they first appeared in the thymus, spleen and liver rather than in the bone marrow after transplantation of MISTRG mice with human CD34+ hematopoietic stem and progenitor cells. Due to their strategic location, human CD5+ ILCs could serve as blood-borne sentinels, ready to be recruited into the lung to respond to environmental challenges. This work emphasizes the uniqueness of human CD5+ ILCs in terms of their anatomical localization and developmental origin compared to well-studied CD5- ILCs.